Feasibility of Ultrasound-Guided Sacroiliac Joint Injections in Children Presenting with Sacroiliitis - Klauser, A. S.; Sailer-Hoeck, M.; Abdellah, M. M. H.; Taljanovic, M. S.; Siedentopf, C.; Auer, T.; Brunner, J.; Jaschke, W. R. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: To evaluate the feasibility and effectiveness of US-guided sacroiliac joint injection in the treatment of sacroiliitis in children.Materials and Methods: This study was approved by the institutional review board and informed oral and written consent was obtained from the patients and their parents. In 13 patients (7 females and 6 males), 9 – 16 years (mean +/– std 11.39 +/–1.98), 18 sacroiliac joint (SI joint) injections were performed under US guidance. All patients suffered from severe sacroiliitis. US scanning was performed using a linear-array transducer operating at 5 – 18 MHz. Rating of the patients pain using a 0 – 10 dolorimetry scale on a visual analog score (VAS) was recorded before, immediately after and 3 months after injection to monitor severity and therapeutic response.Results: Injection could be performed in all patients without complication and showed good response immediately and 3 months after the injection with a decrease of the VAS (from mean +/– std 9.44 +/– 1.097 to 3.89 +/– 3.82, p < 0.001 and to 0.56 +/– 1.097, p < 0.05, respectively).Conclusion: US-guided SI joint injection was feasible in all children, relatively quick and easy to perform and appeared effective in the treatment of children with sacroiliitis.
Keywords: pelvis; interventional procedures; ultrasound; inflammation